Metal ions in non-complementary DNA base pairs: an ab initio study of Cu(I), Ag(I), and Au(I) complexes with the cytosine-adenine base pair - Sponer, J; Sabat, M; Burda, J V; Leszczynski, J; Hobza, P; Lippert, B (Journal of biological inorganic chemistry, 1999)
Ab initio calculations have been carried out to characterize the structure and energetics of a silver(I) complex with the cytosine-adenine DNA base pair and an aqua ligand in the coordination sphere of Ag. In addition, we have also studied analogous complexes with Cu(I) and Au(I), and structures in which adenine has been replaced by purine in order to investigate the structural role of the adenine amino group. The calculations revealed that all metal-modified structures are dominated by the metal-base interactions, while the water-metal ion interaction and many-body interligand repulsion are less important contributions. Nevertheless, the structural role of the water molecule in the complex is quite apparent and in agreement with an earlier crystallographic study. The metal-modified base pairs exhibit large conformational flexibility toward out-of-plane motions (propeller twist and buckle), comparable or, in some cases, even larger than that observed in the base pairs without metal ions. All structures have been optimized within the Hartree-Fock approximation, while interaction energies were evaluated with the inclusion of electron correlation.
Keywords: Cytosine; molekulární struktura; Adenine; Molecular Structure; adenin; Metals; měď; Copper; Base Pair Mismatch; Gold; Silver; zlato; kovy; stříbro; cytosin; chybné párování bází